Acces by KAI: Mobile E-Commerce to Increase Company Revenue - Gifari, Nur Rahmat; Oktaviyah, Nurafni (Universitas Negeri Makassar, 2024)
The speed of development in the fields of information technology and telecommunications in the current era is able to provide very significant changes in every element of life, one of which is the transportation sector. Almost all transportation service providers seem to be forced to improvise existing technological developments, either in whole or in part. Access by KAI is an official application provided by PT. KAI as a tool to fulfill the needs of application- based users of railway transportation services in Indonesia. The aim of this research is to gain a deeper understanding regarding the implementation of the management information system in the Access by KAI application. The research method used in this article is a qualitative descriptive method, where a literature review and literature review is carried out in the form of theoretical analysis, previous research findings, and references related to the topic discussed as the main data source. The research results place Access by KAI as an application that makes information technology and management information the main axis in carrying out business activities, starting from more efficient service operations to supporting tools in decision making.Kecepatan perkembangan dalam bidang teknologi informasi serta telekomunikasi pada era saat ini mampu memberikan perubahan yang sangat signifikan pada setiap unsur kehidupan yang dimana salah satu diantaranya yaitu pada bidang transportasi. Hampir seluruh pelaku penyedia layanan jasa transportasi seakan-akan dipaksa untuk melakukan improvisasi terhadap perkembangan teknologi yang ada baik secara keseluruhan maupun sebagian. Acces by KAI merupakan sebuah aplikasi resmi yang disediakan oleh PT. KAI sebagai alat pemenuhan kebutuhan pengguna jasa transportasi perkereta-apian di Indonesia yang berbasis aplikasi. Tujuan penelitian ini ialah untuk mendapatkan pemahaman yang lebih mendalam terkait pengimplementasian sistem informasi manajemen pada aplikasi Acces by KAI. Metode penelitian yang digunakan dalam artikel ini adalah metode deskriptif kualitatif, dimana dilakukan tinjauan pustaka dan kajian literatur berupa analisis teori, temuan penelitian terdahulu, dan referensi terkait topik yang dibahas sebagai sumber data utama. Hasil penelitian menempatkan Acces by KAI sebagai aplikasi yang menjadikan teknologi informasi serta informasi manajemen sebagai poros utama dalam melakukan aktifitas usahanya, mulai dari pengoperasian pelayanan yang lebih efisien hingga sebagai alat pembantu dalam pengambilan keputusan